2017
DOI: 10.1038/s41699-017-0037-z
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-based nanolaminates as ultra-high permeation barriers

Abstract: Permeation barrier films are critical to a wide range of applications. In particular, for organic electronics and photovoltaics not only ultra-low permeation values are required but also optical transparency. A laminate structure thereby allows synergistic effects between different materials. Here, we report on a combination of chemical vapor deposition (CVD) and atomic layer deposition (ALD) to create in scalable fashion few-layer graphene/aluminium oxide-based nanolaminates. The resulting~10 nm contiguous, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…In the case of CVD graphene transferred on to substrates by the polymer method, it has been reported that the presence of polymer residues can cause edge-on orientation for pentacene on graphene [11]. However, in this work, effort has been taken to remove any polymer residues via thermal treatment [30]. Recently, Rafiee et al found, in the context of wetting, that the van der Waals forces are not disrupted by the graphene sheet as it is extremely thin (ca.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of CVD graphene transferred on to substrates by the polymer method, it has been reported that the presence of polymer residues can cause edge-on orientation for pentacene on graphene [11]. However, in this work, effort has been taken to remove any polymer residues via thermal treatment [30]. Recently, Rafiee et al found, in the context of wetting, that the van der Waals forces are not disrupted by the graphene sheet as it is extremely thin (ca.…”
Section: Resultsmentioning
confidence: 99%
“…We find that a general route to overcome many of these issues is to combine 2D and 3D materials in hybrid or compound coatings, i.e. by combining 2D materials with polymers (Yu et al, 2018) or ceramics (Sagade et al, 2017). When embedded in a polymer coating, a 2D material may provide the barrier function, while the other layer(s) will offer other functionalities needed for an effective and longlasting protection.…”
Section: Discussionmentioning
confidence: 99%
“…As neither graphene nor hBN possess all the many diverse and sometimes conflicting properties that are required to effectively protect a metal subject in harsh environments during actual use, it is obvious to turn to hybrid coatings where the two-dimensional materials are coupled with other functional layers made of, for instance, polymers, ceramics (Sagade et al, 2017) or other materials. In this scenario, the 2D materials will provide the barrier function, while the other layers will cover other requirements.…”
Section: The Lab -Reality Gapmentioning
confidence: 99%
“…Furthermore, physical deposition of graphene provides a reliable route towards fabrication of coatings with high optical transparency (>90%), making them suitable for sealing of light-emitting diodes. Graphene nanolaminates grown in this way present remarkable barrier against moisture ingress and demonstrate substantial level of flexibility, as they can be used either alone or in combination with semiconductor oxides [66].…”
Section: The Role Of 2d Materials In Encapsulation Processmentioning
confidence: 99%